Transcription profiling of the cyanobacterium Synechococcus sp. PCC 7002 using high-throughput cDNA sequencing - Ludwig, M.; Bryant, Donald A. (My University, 2011)
The genome of the unicellular, euryhaline cyanobacterium Synechococcus sp. PCC 7002 encodes about 3200 proteins. Transcripts were detected for nearly all annotated open reading frames by a global transcriptomic analysis by Next-Generation (SOLiD™) sequencing of cDNA. In the cDNA samples sequenced, ∼90% of the mapped sequences were derived from the 16S and 23S ribosomal RNAs and ∼10% of the sequences were derived from mRNAs. In cells grown photoautotrophically under standard conditions [38°C, 1% (v/v) CO2 in air, 250 μmol photons m−2 s−1], the highest transcript levels (up to 2% of the total mRNA for the most abundantly transcribed genes; e.g., cpcAB, psbA, psaA) were generally derived from genes encoding structural components of the photosynthetic apparatus. High-light exposure for 1 h caused changes in transcript levels for genes encoding proteins of the photosynthetic apparatus, Type-1 NADH dehydrogenase complex and ATP synthase, whereas dark incubation for 1 h resulted in a global decrease in transcript levels for photosynthesis-related genes and an increase in transcript levels for genes involved in carbohydrate degradation. Transcript levels for pyruvate kinase and the pyruvate dehydrogenase complex decreased sharply in cells incubated in the dark. Under dark anoxic (fermentative) conditions, transcript changes indicated a global decrease in transcripts for respiratory proteins and suggested that cells employ an alternative phosphoenolpyruvate degradation pathway via phosphoenolpyruvate synthase (ppsA) and the pyruvate:ferredoxin oxidoreductase (nifJ). Finally, the data suggested that an apparent operon involved in tetrapyrrole biosynthesis and fatty acid desaturation, acsF2–ho2–hemN2–desF, may be regulated by oxygen concentration.
Keywords: Biochemistry; Microbiology